Degradation of few avean feathers by Microsporum gypseum - Sowjanya, N C; Manohara Chary, C (Journal of Phytology, 2012)
The ability of the keratinophilic fungus Microsporum gypseum to degrade different keratin substrates viz., chicken feathers, pigeon feathers and peacock feathers has been studied under different incubation periods.The amount of net protein (µg/ml) released during the growth of Microsporum gypseum on different keratin substrate reveals that pigeon feathers are most degraded keratin substrate and peacock feathers are least degraded keratin substrate.